Structural ecological connectivity in the municipality of Valparaíso (Caquetá, Colombia): A proposal for linkages and connectivity nuclei at a semi-detailed scale - Jiménez Viasús, John Fredy (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Ecosystem services are the benefits that humanity receives from ecosystems: from the provision of food, water, wood and fiber to water and climate regulation, among many others. In order to maintain this environmental supply, it is necessary to know the location, state and degree of connection of the natural areas present in a territory. Taking into account the interpretation of land cover at a scale of 1:25,000, the delimitation of sub-basins within the municipality, the consultation of secondary information, the use of the Linkage Mapper tool and a subsequent verification with satellite images of the year 2020, a set of linkages and structural connectivity cores are proposed for the natural areas present in the municipality of Valparaíso (Caquetá) in Colombia, in order to provide decision-makers with inputs for land management in order to maintain the quality and supply of ecosystem services. As a result, 48 connectivity cores were obtained corresponding to inland and floodable forests and about 7% of the municipal area in linkages that are mainly represented by remaining gallery forests in the study area.